2017
DOI: 10.1016/j.celrep.2017.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Purine Nucleotide Availability Regulates mTORC1 Activity through the Rheb GTPase

Abstract: Pharmacologic agents that interfere with nucleotide metabolism constitute an important class of anticancer agents. Recent studies have demonstrated that mTOR complex 1 (mTORC1) inhibitors suppress de novo biosynthesis of pyrimidine and purine nucleotides. Here, we demonstrate that mTORC1 itself is suppressed by drugs that reduce intracellular purine nucleotide pools. Cellular treatment with AG2037, an inhibitor of the purine biosynthetic enzyme GARFT, profoundly inhibits mTORC1 activity via a reduction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
98
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 47 publications
12
98
2
Order By: Relevance
“…Interestingly, 16-hour treatment with AVN-944 depleted guanylates but not adenylates and lead to decreased Rheb protein levels in A549 cells, which were rescued with excess exogenous guanine, partially at 1 hour and fully when co-treated for the 16-hours with AVN-944 (Figure 7A, 7B, and S7A), the paradigm used by Emmanuel et al (Emmanuel et al, 2017). However, our laboratory stock of A549 cells exhibited complete resistance to this compound for effects on mTORC1 signaling, even at doses 10-fold higher than that which leads to Rheb depletion, further demonstrating a separation of the Rheb effects from those on mTORC1 (Figure 7C).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Interestingly, 16-hour treatment with AVN-944 depleted guanylates but not adenylates and lead to decreased Rheb protein levels in A549 cells, which were rescued with excess exogenous guanine, partially at 1 hour and fully when co-treated for the 16-hours with AVN-944 (Figure 7A, 7B, and S7A), the paradigm used by Emmanuel et al (Emmanuel et al, 2017). However, our laboratory stock of A549 cells exhibited complete resistance to this compound for effects on mTORC1 signaling, even at doses 10-fold higher than that which leads to Rheb depletion, further demonstrating a separation of the Rheb effects from those on mTORC1 (Figure 7C).…”
Section: Resultsmentioning
confidence: 75%
“…The study by Emmanuel et al (Emmanuel et al, 2017) also demonstrated that mTORC1 signaling is sensitive to purine nucleotides. However, the authors conclude that mTORC1 activity is inhibited by guanylate depletion through effects on Rheb-GTP binding and farnesylation leading to loss of Rheb lysosomal localization.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations